Effects of Perceived Autonomy Support in the Physical Education on Basic Psychological Needs Satisfaction, Intrinsic Motivation and Intention to Perform Physical Activity in High School Students - Fatemeh Beigom Hosseini; Saeed Ghorbani; Reza Rezaeeshirazi (Shiraz University of Medical Sciences, 2020)
Background: Finding factors or conditions that could increase the level of physical activity in students is a controversial topic concerning school health. We conducted the current research to investigate the effects of perceived autonomy support in physical education class on intrinsic motivation and intention to participation of high-school students in leisure-time physical activity. Gender differences were also reported. Methods: This study utilized a descriptive-correlation approach. Our participants comprised 400 high school students, including 100 tenth-grade boys, 100 eleventh-grade boys, 100 tenth-grade girls and 100 eleventh-grade girls, from Aliabad Katoul, Golestan, Iran, in 2019. The data was collected using standard questionnaires. We employed structural equation method to examine the associations between variables, and analysis of variance (ANOVA) to examine the gender differences. Results: Descriptive statistics showed that boys and girls of the same grade had almost identical age. The results of path analysis revealed that perceived autonomy support positively influenced psychological need satisfaction and intrinsic motivation (T=1.96 and T=2.09, respectively). Moreover, psychological need satisfaction positively affected intrinsic motivation in physical education class (T=15.23). Furthermore, intrinsic motivation in physical education class was transferred to intrinsic motivation in leisuretime (T=6.82). Intrinsic motivation in leisure-time positively affected the inclination to perform physical activity outside school (T=7.05). Finally, boys were observed to have higher perceived autonomy, higher motivation and be more willing to do physical activity compared to girls (p <0.001). Conclusions: Perceived autonomy support plays an important role in motivating students to be physically active. We discussed our results based on the self-determination theory. Practical and clinical implications were presented to physical education teachers and physicians.